(untitled) (Journal of the College of Basic Education, 2022)
This study conducted to examine the effect of two newly synthesized compounds[3-(5-(ethylthio)-1,3,4-thiadiazol-2-yl)-2,3-dihydro-2-(3-nitrophenyl)benzo[1-3-e] thiazin-4-one (compound I) and 5(4-dimethyl amino) benzylidene amino)-1,3,4-thiadiazole-2-thiol(compound II)] as antiatherogenic and antioxidant agents, In vivo study.